2015
DOI: 10.1007/s13277-015-3753-z
|View full text |Cite
|
Sign up to set email alerts
|

Speckle-type POZ protein is negatively associated with malignancies and inhibits cell proliferation and migration in liver cancer

Abstract: Speckle-type POZ protein (SPOP) is an E3 ubiquitin ligase adaptor that is frequently mutated in human cancers. Our previous findings have indicated that SPOP is mutated and functions as a novel tumor suppressor in hepatoblastoma (HB). However, the biological roles and clinical significance of this SPOP in hepatocellular carcinoma (HCC) remain unknown. In this study, we found that the expression level of SPOP was downregulated in HCC primary tumors by quantitative real-time PCR and the protein level of SPOP was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“… 23 Similarly, SPOP has also been reported to inhibit the proliferation and migration of liver cancer cells. 24 On the contrary, the results of the colony formation assay in the current study indicated that silencing SPOP inhibited the colony formation ability. The trans-well migration assay also indicated that silencing SPOP attenuated the migration ability of the RCC cells.…”
Section: Discussioncontrasting
confidence: 67%
“… 23 Similarly, SPOP has also been reported to inhibit the proliferation and migration of liver cancer cells. 24 On the contrary, the results of the colony formation assay in the current study indicated that silencing SPOP inhibited the colony formation ability. The trans-well migration assay also indicated that silencing SPOP attenuated the migration ability of the RCC cells.…”
Section: Discussioncontrasting
confidence: 67%
“…Although HB and HCC are the most common malignant pediatric liver tumors and are characterized by aggressive growth and early metastasis, the molecular mechanisms underlying their development remain largely unknown [38]. Numerous oncogenic molecules and signaling pathways are co-regulated by functionally-related TFs and associated genes [39].…”
Section: Discussionmentioning
confidence: 99%
“…As a common malignant tumor among tumors of children, the prognosis of hepatoblastoma is often related to the type of disease differentiation. Although many genes and pathways have been studied in HB, the speci c molecular mechanism has not been revealed 22 . It has been demonstrated that the miR-100/let-7a-2/miR-125b-1 cluster works with miR-371-3 in HB.…”
Section: Discussionmentioning
confidence: 99%